The cultivation regimes of Morchella sextelata trigger shifts in the community assemblage and ecological traits of soil bacteria - Zhang, Yan; Zhao, Qi; Uroz, Stéphane; Gao, Tianpeng; Li, Jing; He, Fengqin; Rosazlina, Rusly; Martin, Francis; Xu, Lingling (Frontiers in Microbiology, 2023)
The successful large-scale cultivation of morel mushrooms (Morchella sextelata) requires a comprehensive understanding of the soil bacterial communities associated with morel-farming beds, as the interactions between fungi and bacteria play a crucial role in shaping the soil microbiome. In this study, we investigated the temporal distribution and ecological characteristics of soil bacteria associated with morel fruiting bodies at different stages, specifically the conidial and primordial stages, under two cropping regimes, non-continuous cropping (NCC) and continuous cropping (CC). Our findings revealed a significant reduction in the yield of morel primordia during the third year following two years of CC (0.29 ± 0.25 primordia/grid), in comparison to the NCC regime (12.39 ± 6.09 primordia/grid). Furthermore, inoculation with morel mycelia had a notable impact on soil bacterial diversity, decreasing it in the NCC regime and increasing the number of generalist bacterial 2 This is a provisional file, not the final typeset article members in the CC regime. The latter regime also led to the accumulation of nutrients in the soil beds, resulting in a shift from a stochastic to a deterministic process in the composition of the bacterial community, which differed from the NCC regime. Additionally, mycelial inoculation had a positive effect on the abundance of potential copiotrophic/denitrifying and N-fixing bacteria while decreasing the abundance of oligotrophic/nitrifying bacteria. Interestingly, this effect was more pronounced in the NCC regime than in the CC regime. These results suggest that the increase in potential copiotrophic/nitrifying and N-fixing bacteria facilitated the decomposition of nutrients in exogenous nutrient bags by morel mushrooms, thereby maintaining nitrogen balance in the soil. Overall, our study provides valuable insights into the interactions between morel mycelia and the associated soil bacteriome as well as the influence of different cultivation regimes on these interactions. These findings contribute to our understanding of the complex dynamics of the soil microbiome and can inform strategies for optimizing morel mushroom cultivation.